Indoor multipath effect study on the Locata system - Bonenberg, Lukasz K.; Hancock, Craig M.; Roberts, Gethin W. (De Gruyter, 2010)
GNSS has become one of the most wide- spread measurement technologies, allowing cm-level positioning accuracy using RTK or Network RTK. Unfortunately, the system’s major drawbacks are the requirement for a clear view of the sky and accu- racy dependent on the geometric distribution of the satellites, not only varying throughout the day but also prone to location specific problems. With wide- spread utilisation of GNSS for monitoring of man- made structures and other civil engineering tasks, such shortcomings can be critical. One of possible solution is the deployment of a sup- porting system, such as Locata – a terrestrial posi- tioning technology, which mitigates the need for a clear view of the sky and provides system integrity control. This paper, part of the proposed integration feasibil- ity study, presents Locata performance indoors, its capacity and mitigation methods.